Role of Hydrogen Sulfide in Inflammatory Bowel Disease - Nathalie Stummer; René G. Feichtinger; Daniel Weghuber; Barbara Kofler; Anna M. Schneider (MDPI AG, 2023)
Hydrogen sulfide (H2S), originally known as toxic gas, has now attracted attention as one of the gasotransmitters involved in many reactions in the human body. H2S has been assumed to play a role in the pathogenesis of many chronic diseases, of which the exact pathogenesis remains unknown. One of them is inflammatory bowel disease (IBD), a chronic intestinal disease subclassified as Crohn's disease (CD) and ulcerative colitis (UC). Any change in the amount of H2S seems to be linked to inflammation in this illness. These changes can be brought about by alterations in the microbiota, in the endogenous metabolism of H2S and in the diet. As both too little and too much H2S drive inflammation, a balanced level is needed for intestinal health. The aim of this review is to summarize the available literature published until June 2023 in order to provide an overview of the current knowledge of the connection between H2S and IBD.